Identification and characterization of novel antimicrobial peptides from Camelus dromedarius: a combined bioinformatics and experimental study - Al-Mamari, Wafa; Elhag, Yasmin; Al Bulushi, Samir; Rekha, Rokeya S.; Mörman, Cecilia; Bergman, Peter; Al-Ansari, Aliya; Al-Adwani, Salma (Frontiers in Immunology, 2026)
There is an urgent need for new antimicrobial agents to address the emerging antimicrobial resistance and the lack of novel antibiotics on the market. Antimicrobial peptides (AMPs) have gained significant interest as potential antibiotics over the past 30 years due to their broad activity against bacteria. So far, the presence, characteristics, and function of AMPs in camel immunity remain to be explored. Therefore, this study aims to identify and functionally characterize AMPs in Camelus Dromedarius using in-silico and experimental approaches. In-silico identification and prediction of cathelicidin peptides properties were conducted using Blastp, Conserved Domain, Signal P-5.0, Peptide Cutter-Expasy, and the Antimicrobial Sequence Scanning System (AMPA) database. Physicochemical and biological properties were characterized using bioinformatics analysis tools. The experimental assays of synthetic AMPs were performed using circular dichroism (CD) spectroscopy, colony-forming assay, sytox green uptake assay, transmission and scanning electron microscopy, and hemolysis assay. Three cathelicidin peptides were identified from Camelus Dromedarius which were designated as CdPMAP-23, Cdprotegrin-3 (CdPG-3), and Cdcathelin-like (CdCATH). CdPG-3 and CdCATH demonstrated significant antibacterial effects against all tested Gram-negative and Gram-positive strains, including Escherichia. coli (Multidrug resistant) and Methicillin-Resistant Staphylococcus aureus (ATCC 700699). These two peptides caused significant membrane leakage and damage to Escherichia. coli (ATCC 25922), with CdPMAP-23 showing a lesser effect. Lower concentrations of CdPMAP-23, CdPG-3 and CdCATH exhibited low to moderate lytic activity against red blood cells in humans, camels, and chickens. This study identified novel AMPs from dromedary camels with potential therapeutic value against multidrug-resistant strains. The results show that AMPs are present in dromedary camels, setting out a foundation for further studies on the unique features of their innate immune system.